2016
DOI: 10.4103/1596-3519.172559
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcome of renal admissions at the University of Port Harcourt Teaching Hospital, Nigeria: A 4 years review

Abstract: Background/Objective:Renal diseases constitute an enormous health burden globally, more so in developing countries. This report determines the patterns and outcomes of renal diseases in the medical wards of the University Teaching Hospital in Nigeria.Methods:A retrospective study of patients admitted for renal disease in 4 years.Results:A total of 3841 patients were admitted to the medical wards, of which 590 (15.4%) had renal disease. Mean age of patients was 46 ± 15 years. Median duration of admission was 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
3
3
0
Order By: Relevance
“…This single-center, retrospective study found that NCDs account for 66.1% of total admissions and the number of cases of NCDs was two times more compared to CDs (ratio 2:1). A number of studies performed in low and middle income countries have also reported similar findings [7][8][9][10][11] the medical ward of a tertiary center in Nigeria and reported same trend 13 . Again, evidences show that the detection and treatment rate of DM and HTN is inadequate among bangladeshi population .…”
Section: Discussionsupporting
confidence: 52%
“…This single-center, retrospective study found that NCDs account for 66.1% of total admissions and the number of cases of NCDs was two times more compared to CDs (ratio 2:1). A number of studies performed in low and middle income countries have also reported similar findings [7][8][9][10][11] the medical ward of a tertiary center in Nigeria and reported same trend 13 . Again, evidences show that the detection and treatment rate of DM and HTN is inadequate among bangladeshi population .…”
Section: Discussionsupporting
confidence: 52%
“…Our findings in this study are supported by earlier studies, which reported higher proportions of renal disease death attributable to infectious and cardiac deaths . In a retrospective study conducted to determine pattern and outcome of renal admissions at Port Harcourt Teaching Hospital in Nigeria, hypertensive nephropathy, diabetic nephropathy, chronic glomerulonephritis and HIV‐related renal disease were the common causes of death …”
Section: Discussionsupporting
confidence: 89%
“…Unachukwu et al reported same trend [7]. Work by Wachukwu et al found a renal disease prevalence of 15.4% in tandem with the renal disease prevalence found in this study [11]. Other works in tertiary centres in neighbouring south-east, Nigeria reported cardiovascular diseases as leading causes of medical ward admissions [9,12].…”
Section: Discussionsupporting
confidence: 82%